Atomic Layer Deposition Coating of TiO2 Nano-Thin Films on Magnesium-Zinc Alloys to Enhance Cytocompatibility for Bioresorbable Vascular Stents - Yang F (Dove Medical Press, 2019)
Fan Yang, Run Chang, Thomas J Webster Department of Chemical Engineering, Northeastern University, Boston, MA 02115, USACorrespondence: Thomas J WebsterDepartment of Chemical Engineering, Northeastern University, 313 Snell Engineering Center, 360 Huntington Avenue, Boston, MA 02115, USATel +1 617 373 6585Email th.webster@neu.eduBackground and purpose: A coronary stent is a well-known cardiovascular medical device implanted to resolve disorders of the circulatory system due to bloodstream narrowing. Since the implanted device interacts with surrounding biological environments, the surface properties of a typical implantable stent play a critical role in its success or failure. Endothelial cell adhesion and proliferation are fundamental criteria needed for the success of a medical device. Metallic coronary stents are commonly used as biomaterial platforms in cardiovascular implants. As a new generation of coronary stents, bioresorbable vascular scaffolds have attracted a great deal of attention among researchers and studies on bioresorbable materials (such as magnesium and zinc) remain a target for further optimization. However, additional surface modification is needed to control the biodegradation of the implant material while promoting biological reactions without the use of drug elution.Methods: Herein, precise temperature and thickness controlled atomic layer deposition (ALD) was utilized to provide a unique and conformal nanoscale TiO2 coating on a customized magnesium-zinc stent alloy.Results: Impressively, results indicated that this TiO2 nano-thin film coating stimulated coronary arterial endothelial cell adhesion and proliferation with additional features acting as a protective barrier. Data revealed that both surface morphology and surface hydrophilicity contributed to the success of the ALD nanoscale coating, which further acted as a protection layer inhibiting the release of harmful degradation products from the magnesium-zinc stent.Conclusion: Overall, the outcome of this in vitro study provided a promising ALD stent coating with unique nano-structural surface properties for increased endothelialization, and as a result, ALD should be further studied for numerous biomedical applications.Keywords: atomic layer deposition, titanium dioxide, magnesium, bioresorbable vascular scaffold, endothelium, cytocompatibility